The mental health of first- and second-generation migrant vs. native healthcare workers during the COVID-19 pandemic: The VOICE survey of 7,187 employees in the German healthcare sector - Herold, Regina; Morawa, Eva; Schug, Caterina; Geiser, Franziska; Beschoner, Petra; Jerg-Bretzke, Lucia; Albus, Christian; Weidner, Kerstin; Hiebel, Nina; Borho, Andrea; Erim, Yesim (Transcultural Psychiatry, 2024)
The COVID-19 pandemic exacerbated the challenging working conditions of healthcare workers (HCWs) in many regions. A considerable proportion of HCWs in Germany are migrants facing additional migration-related stressors. The aim of this cross-sectional web-based survey was to examine depressive and generalized anxiety symptoms among migrant and native HCWs in Germany during the pandemic. We compared 780 migrant (first- and second-generation) HCWs from different backgrounds with 6,407 native HCWs. Multiple linear regression analyses were used to examine associations between occupational and COVID-19 related variables, controlling for sociodemographics. Migrant HCWs from low-/middle-income countries more frequently had clinically relevant depressive symptoms (PHQ-2 ≥ 3) than did those from high-income countries (29.9% vs. 16.7%, p =.002, ϕ =.156) (all other ϕs/Cramer's Vs ≤.036). There were no clinically relevant differences in anxiety levels (GAD-2 ≥ 3) between native vs. migrant HCWs, native vs. the individual migrant HCW groups, or between the sexes (all ϕs/Cramer's Vs ≤.036). After controlling for key sociodemographic characteristics, native HCWs did not differ from the individual migrant HCW groups on depression and anxiety severity (depression: all βs ≤ |.030|, anxiety: all βs ≤ |.014|). A high percentage of HCWs reported distress, with migrants from low-/middle-income countries reporting highest burden. The results indicate the need to establish prevention programmes for HCWs, with special consideration to vulnerable populations including certain migrant groups.
CRIS-Team Scopus Importer:2024-08-09
Keywords: anxiety; COVID-19; depression; healthcare workers; mental health; migrants